Rodent models in translational circadian photobiology - Tir, Selma; Steel, Laura C.E.; Tam, S.K.E.; Semo, Ma'ayan; Pothecary, Carina A.; Vyazovskiy, Vladyslav V.; Foster, Russell G.; Peirson, Stuart N. (Circadian and Visual Neuroscience, 2022)
Over the last decades remarkable advances have been made in the understanding of the photobiology of circadian rhythms. The identification of a third photoreceptive system in the mammalian eye, in addition to the rods and cones that mediate vision, has transformed our appreciation of the role of light in regulating physiology and behavior. These photosensitive retinal ganglion cells (pRGCs) express the blue-light sensitive photopigment melanopsin and project to the suprachiasmatic nuclei (SCN)—the master circadian pacemaker—as well as many other brain regions. Much of our understanding of the fundamental mechanisms of the pRGCs, and the processes that they regulate, comes from mouse and other rodent models. Here we describe the contribution of rodent models to circadian photobiology, including both their strengths and limitations. In addition, we discuss how an appreciation of both rodent and human data is important for translational circadian photobiology. Such an approach enables a bi-directional flow of information whereby an understanding of basic mechanisms derived from mice can be integrated with studies from humans. Progress in this field is being driven forward at several levels of analysis, not least by the use of personalized light measurements and photoreceptor specific stimuli in human studies, and by studying the impact of environmental, rather than laboratory, lighting on different rodent models.